Analysis of Islamic Bank Involvement in Supporting Local Brand of MSME Category in Medan to Welcome the Demographic Bonus Era - Makarim, Naylatussalwa; Harahap, Rahmat Daim; Daulay, Aqwa Naser (Amkop Management Accounting Review (AMAR), 2025)
This study analyzes the involvement of Islamic banks in supporting the brand development of local MSMEs in Medan City during the demographic bonus era. Using a descriptive qualitative approach and content analysis, this study utilized primary data from semi-structured interviews with three Islamic banks (Bank Muamalat, Bank Syariah Indonesia, and BTPN Syariah) and secondary data from reports, media documentation, and academic publications.Findings show variations in bank engagement. The research results from the comparison of these three Islamic banks using the content analysis method, found that Bank Syariah Indonesia (BSI) showed the highest engagement of the other two banks, amounting to (46.12%) through comprehensive strategies, including UMKM Center, halal certification, expansion of digital transactions, and access to global markets. BTPN Syariah followed with (39.16%), distinguished by its focus on empowering low-income women through PRS and collateral-free financing to strengthen financial literacy and self-reliance of rural women. Bank Muamalat recorded the lowest engagement (14.72%), with an emphasis on community-based social programs such as Gerobak Usaha and Food Court Berdaya, which foster local economic solidarity. The study concludes that the three Islamic banks' support for MSMEs goes beyond financing and reflects their distinctive institutional strategies. BSI takes the lead in modernization and market expansion, BTPN Syariah highlights women empowerment, while Bank Muamalat contributes through grassroots community initiatives. Synergies between these approaches are critical to building a layered, competitive and sustainable MSME ecosystem.